Phytoestrogen consumption from foods and supplements and epithelial ovarian cancer risk: a population-based case control study - Paddock Lisa E; Chandran Urmila; King Melony; Bandera Elisa V; Rodriguez-Rodriguez Lorna; Olson Sara H (BMC, 2011)
Abstract Background While there is extensive literature evaluating the impact of phytoestrogen consumption on breast cancer risk, its role on ovarian cancer has received little attention. Methods We conducted a population-based case-control study to evaluate phytoestrogen intake from foods and supplements and epithelial ovarian cancer risk. Cases were identified in six counties in New Jersey through the New Jersey State Cancer Registry. Controls were identified by random digit dialing, CMS (Centers for Medicare and Medicaid Service) lists, and area sampling. A total of 205 cases and 390 controls were included in analyses. Unconditional logistic regression analyses were conducted to examine associations with total phytoestrogens, as well as isoflavones (daidzein, genistein, formononetin, and glycitein), lignans (matairesinol, lariciresinol, pinoresinol, secoisolariciresinol), and coumestrol. Results No statistically significant associations were found with any of the phytoestrogens under evaluation. However, there was a suggestion of an inverse association with total phytoestrogen consumption (from foods and supplements), with an odds ratio (OR) of 0.62 (95% CI: 0.38-1.00; p for trend: 0.04) for the highest vs. lowest tertile of consumption, after adjusting for reproductive covariates, age, race, education, BMI, and total energy. Further adjustment for smoking and physical activity attenuated risk estimates (OR: 0.66; 95% CI: 0.41-1.08). There was little evidence of an inverse association for isoflavones, lignans, or coumestrol. Conclusions This study provided some suggestion that phytoestrogen consumption may decrease ovarian cancer risk, although results did not reach statistical significance.